Warrior dreams: violence and manhood in post-Vietnam America - Gibson, James William (Hill and Wang, 1994)
Vietnam signaled the end of America's long history of martial victories. In Warrior Dreams, James William Gibson argues that the shame of defeat by a technologically inferior enemy, compounded by challenges to the status quo from feminism and minority groups, created a profound crisis in American identity - particularly for the white American male - and gave birth to a disturbing and reactionary new war culture designed to make America well again. Armed with a journalist's curiosity and a critic's precision, Gibson sets out to map this new American war zone. He plays paintball with Los Angeles's weekend warriors, learns to shoot like a pro at Arizona's elite Gunsite Ranch, and parties with soldiers of fortune at their annual convention in Las Vegas. Gibson surveys the combat magazines and weapons advertisements, films and novels that fuel the sexual, violent fantasies of millions of would-be warriors across the country. And he shows how this mythology, far from harmless consumer entertainment, has indeed started a new war with real warriors - Aryan Nation, contract killers, mercenaries in Central America - and with dangerous consequences for our democracy